2017
DOI: 10.1007/s12298-017-0430-2
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous application of rutin and gallic acid regulate antioxidants and alleviate reactive oxygen generation in Oryza sativa L.

Abstract: The effect of rutin and gallic acid on growth, phytochemical and defense gene activation of rice ( L.) was investigated. The seeds of rice were primed with different concentrations of rutin and gallic acid (10-60 µg mL) to explicate the effect on germination on water agar plates. Further, to study the effect of most effective concentrations of gallic acid (60 µg mL) and rutin (50 µg mL), greenhouse pot experiment was set up to determine the changes in growth, antioxidant and defense parameters. The results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 49 publications
12
26
0
Order By: Relevance
“…Rutin improved creeping bentgrass responses to heat stress via enhanced TQ and CHL but did not have a major effect on lipid peroxidation or antioxidant enzyme activities or fatty acid composition of leaf tissues. Similar results were found by Singh et al (2017), as the total antioxidant capacity of rice plants treated with rutin were not significantly different from control plants but the ROS levels were lower in rutin-treated plants. Rutin is thought to interact with phospholipids at the lipidwater interface and reduce oxidative stress of lipids (Agati et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Rutin improved creeping bentgrass responses to heat stress via enhanced TQ and CHL but did not have a major effect on lipid peroxidation or antioxidant enzyme activities or fatty acid composition of leaf tissues. Similar results were found by Singh et al (2017), as the total antioxidant capacity of rice plants treated with rutin were not significantly different from control plants but the ROS levels were lower in rutin-treated plants. Rutin is thought to interact with phospholipids at the lipidwater interface and reduce oxidative stress of lipids (Agati et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…The strong antioxidant properties of GA (#2), and its derivatives, have been reported in literature, and several studies claim the possible role and application of GA in plant nutrition at different stages of growth, especially in early root and plant development 26,27 . For example, Singh and co-workers showed that the application of exogenous GA on rice seeds led to an increase of root length compared to the control 27 . Moreover, Negi and colleagues showed that GA might have an auxin-like function, directly acting on root length and development 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, ferulic acid reacts as a natural protector against ultra-violet radiation known to cause skin disorders such as cancer and acceleration of skin aging. Rutin and gallic acid also help to strengthen veins and to inhibit the formation of amyloid fibrils, the principal causes of Alzheimer's diseases, respectively (Singh et al, 2017).…”
Section: Liquid Chromatography Coupled To Mass Spectrometry (Lc/ms)mentioning
confidence: 99%